Industrial application of eutectic freeze crystallization - Jivanji, Rineshkumar Bharat (Department of Chemical Engineering, 2015)
South African industries are currently generating increasing quantities of hypersaline brine streams. These wastewater streams need to be processed in an ecologically friendly and economically favourable method to produce both purified water and salts.